Sistemas legais de medidas de peso e capacidade : do condado portucalense ao século XVI - Lopes, Luís Seabra (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The evolution of the legal systems of weights and capacity measures used in Portugal from the end of the 11th century to the 16th century is described. Unlike previous literature on this subject, this paper pays particular attention to studying the equivalences of the ancient Portuguese weights and measures to the current international system of units.